The development and exploratory analysis of the Back Pain Attitudes Questionnaire (Back-PAQ). Issue 5 (23rd May 2014) - Darlow, Ben; Perry, Meredith; Mathieson, Fiona; Stanley, James; Melloh, Markus; Marsh, Reginald; Baxter, G David; Dowell, Anthony
Abstract : Objectives: To develop an instrument to assess attitudes and underlying beliefs about back pain, and subsequently investigate its internal consistency and underlying structures. Design: The instrument was developed by a multidisciplinary team of clinicians and researchers based on analysis of qualitative interviews with people experiencing acute and chronic back pain. Exploratory analysis was conducted using data from a population-based cross-sectional survey. Setting: Qualitative interviews with community-based participants and subsequent postal survey. Participants: Instrument development informed by interviews with 12 participants with acute back pain and 11 participants with chronic back pain. Data for exploratory analysis collected from New Zealand residents and citizens aged 18 years and above. 1000 participants were randomly selected from the New Zealand Electoral Roll. 602 valid responses were received. Measures: The 34-item Back Pain Attitudes Questionnaire (Back-PAQ) was developed. Internal consistency was evaluated by the Cronbach α coefficient. Exploratory analysis investigated the structure of the data using Principal Component Analysis. Results: The 34-item long form of the scale had acceptable internal consistency (α=0.70; 95% CI 0.66 to 0.73). Exploratory analysis identified five two-item principal components which accounted for 74% of the variance in the reduced data set: 'vulnerability of the back'; 'relationship between back pain and injury'; 'activity participation while experiencing back pain'; 'prognosis of back pain' and 'psychological influences on recovery'. Internal consistency was acceptable for the reduced 10-item scale (α=0.61; 95% CI 0.56 to 0.66) and the identified components (α between 0.50 and 0.78). Conclusions: The 34-item long form of the scale may be appropriate for use in future cross-sectional studies. The 10-item short form may be appropriate for use as a screening tool, or an outcome assessment instrument. Further testing of the 10-item Back-PAQ's construct validity, reliability, responsiveness to change and predictive ability needs to be conducted.